Relationships between self-esteem, parent-child relationship, social support and life satisfaction among Iranian adolescents in Kuala Lumpur, Malaysia - Azharkamandi, Ayda (2018)
In recent decades, Positive Psychology especially Life Satisfaction among adolescent has become considerably more common phenomenon in behavioral science research. According to the statistics and reports, more than half of adolescents reported feelings of dissatisfaction of their life and the rate of life satisfaction among Iranian adolescents living abroad is two times less in comparison with others. Numerous studies have investigated the underlying factors of life satisfaction among adolescent. Nonetheless, very few researches have focused on satisfaction of life among adolescent living in foreign countries. This study examined the effect of self-steem, parent-child relationship (father-child relationship, mother-child relationship) and social support on life satisfaction among Iranian adolescent living in Kuala Lumpur, Malaysia. The study also examined the mediating role of self-esteem in the relationships between social support and parent-child relationship with life satisfaction separately. As this study is among Iranian children who came temporarily to foreign country, background information such as age, gender, length of stay in Malaysia, number of sibling, and family income have been considered. This study is a quantitative study which employs a cross-sectional research design. A total of 175 respondents (90 female and 85 male) aged between 12 to 18 years old that were available during the study period, involved in the study. Data was collected using self-administered questionnaire such as Life Scale (SWLS) ( Diener, Emmons, Larsen & Griffin, 1985) , Parent-Child Relationship Survey (PCRS) (Fine, Worley & Schwebel, 1985), self-esteem scale (Rosenberg, 1965), and Multidimensional scale of perceived social support (MSPSS) (Zimet, Dahlem,, Zimet & Farley, 1988). All the instruments used in this study were highly reliable. Descriptive statistics, independent sample t–test, correlation and regression analysis were conducted; while the mediating effect was analysed using Sobel test (Barron and Kenny approach, 1986). Findings showed that male respondents demonstrated higher life satisfaction than females. Results of correlation analysis showed a significant relationships between all predictor variables with life satisfaction except on age. Results illustrated that almost all variables in regression model were significant predictor of life satisfaction. Finally, results also presented that, self-esteem mediated partially the relationships between social support, father-child relationship, and mother-child relationship with life satisfaction. In conclusion, the findings of the present study revealed the importance of parents in enhancing self-esteem and life satisfaction of Iranian adolescent living in Malaysia. The nature of relationships between independent variables and life satisfaction implied that life satisfaction is important issue among adolescent abroad. Reasonable support from society and warmth and positive relationship from parents may have a significant effect on child’s self-esteem and increasing their life satisfaction. The finding of current study advances the understanding of the importance of selfesteem as an influencing factor against life satisfaction of adolescents. It also contributes towards increased understanding of the importance of external factors such as parent-child relationships and perceived social support as an effective factors in life satisfaction among Iranian adolescents. The findings of the current study may be useful for therapists, parents, adolescents, counsellors, and policy makers in preventing dissatisfaction in adolescence period, which can lead to some difficulties such as academic failure. However, this study is limited to Iranian adolescent (secondary schoolers and high schoolers) living in Malaysia, aged between 12 and 18 years old. Thus, the researcher recommends further study in other region and difference age group to enhance the generalizability.